The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1021/bi990048t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of DnaB Helicase of Escherichia coli:  Structural Domains Involved in ATP Hydrolysis, DNA Binding, and Oligomerization

Abstract: We describe the delineation of three distinct structural domains of the DnaB helicase of Escherichia coli: domain alpha, amino acid residues (aa) 1-156; domain beta, aa 157-302; and domain gamma, aa 303-471. Using mutants with deletion in these domains, we have examined their role(s) in hexamer formation, DNA-dependent ATPase, and DNA helicase activities. The mutant DnaBbetagamma protein, in which domain alpha was deleted, formed a hexamer; whereas the mutant DnaBalphabeta, in which domain gamma was deleted, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 32 publications
5
90
0
Order By: Relevance
“…Evidently, DnaBMut2 was able to provide the functions of the helicase such as translocation on ssDNA template required for successful stimulation of the primase activity. These results were probably a consequence of the fact that mutations R324A and R326A in the RSRARR DNA binding motif of the helicase did not abolish, but significantly reduced the DNA binding and the DNA-dependent ATPase and helicase activities (46). In contrast, DnaBMut1 failed to stimulate the primase activity of the general priming system (Fig.…”
Section: Analysis Of In Vitro Primer Synthesis Carried Out By Primasementioning
confidence: 97%
See 4 more Smart Citations
“…Evidently, DnaBMut2 was able to provide the functions of the helicase such as translocation on ssDNA template required for successful stimulation of the primase activity. These results were probably a consequence of the fact that mutations R324A and R326A in the RSRARR DNA binding motif of the helicase did not abolish, but significantly reduced the DNA binding and the DNA-dependent ATPase and helicase activities (46). In contrast, DnaBMut1 failed to stimulate the primase activity of the general priming system (Fig.…”
Section: Analysis Of In Vitro Primer Synthesis Carried Out By Primasementioning
confidence: 97%
“…Our previous studies suggested that DnaBMut1, with specific mutations R328A and R329A in the RSRARR DNA binding motif exhibit a significant decrease in DNA-dependent ATPase activity and a complete loss of the helicase activity, indicating the important roles of these residues in DNA binding and helicase activity (46). Besides specific mutations, R324A and R326A of DnaBMut2 led to a considerably attenuated DNA binding as well as reduced DNA-dependent ATPase and helicase activities (46). We further addressed the question of how the mutations in RSRARR DNA binding will interfere with the primer synthesis of the general priming system.…”
Section: Analysis Of In Vitro Primer Synthesis Carried Out By Primasementioning
confidence: 99%
See 3 more Smart Citations